50 years of Timişoara architecture school: between tradition and avant-garde - Gaivoronschi, Vlad; Simina, Cuc (project baikal, 2021)
Evaluating a series of important moments which brought together the architects of Timișoara brings into light mechanisms and chances which defined their small universe and their work. By accumulating national and international awards and prizes, by being present in international exhibitions and biennials, Timișoara became an important pole of the Romanian architecture. These dynamics generated three important moments - the presence of Timișoara architects and the Timișoara Architecture Faculty at the Venice Biennial in 1996, the appearance after 2000 of the “De Arhitectura” journal, and in the recent years the first two editions of the Timișoara Euroregional Architecture Biennial “BETA”.
Keywords: Timișoara; Central-European; intercultural; avant-garde; Architecture Faculty; Biennial